2023
DOI: 10.1111/mve.12648
|View full text |Cite
|
Sign up to set email alerts
|

Tick‐borne pathogens in ticks from urban and suburban areas of north‐western Spain: Importance of Ixodes frontalis harbouring zoonotic pathogens

Abstract: To identify the questing tick populations in urban and suburban areas from the city of Lugo (NW Spain), ticks were collected monthly by flagging. The presence of Borrelia spp., Rickettsia spp. and Anaplasma phagocytophilum also was determined by polymerase chain reaction (PCR) and sequence analysis. Overall, 342 questing ticks were collected; the tick abundance was higher in suburban (95.9%) than in urban areas (4.1%). Ixodes frontalis was the most abundant (86.5%); 88.5% were larvae, 11.1% nymphs and 0.3% adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…ricinus tick pools of this study. A similar rate was reported in a study conducted in northern Spain (40%; 10/25) (Remesar et al 2023 ). Nevertheless, our percentage was higher compared with other European studies carried out, for example, in Italy (14%; 30/215) (Cafiso et al 2021 ) or France (1.4%; 10/696) (Akl et al 2019 ).…”
Section: Discussionsupporting
confidence: 89%
“…ricinus tick pools of this study. A similar rate was reported in a study conducted in northern Spain (40%; 10/25) (Remesar et al 2023 ). Nevertheless, our percentage was higher compared with other European studies carried out, for example, in Italy (14%; 30/215) (Cafiso et al 2021 ) or France (1.4%; 10/696) (Akl et al 2019 ).…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, Bl. turdi was found in I. frontalis ticks collected from vegetation of urban and sub-urban areas [ 197 ] as well as in I. frontalis , I. ricinus, and Haemaphysalis punctata ticks collected from passerine birds [ 87 ]. Moreover, Hyalomma lusitanicum ticks from wild ungulates revealed that they were positive for Bl.…”
Section: Lyme Diseasementioning
confidence: 99%